2016
DOI: 10.3109/07435800.2015.1094085
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic association of changes in serum uric acid and triglycerides with changes in insulin resistance after walking exercise in community-dwelling older women

Abstract: Multivariate linear regression analysis showed that baseline TG and γ-glutamyltransferase (GGT) were significantly associated with baseline HOMA-IR. After the 12-week training program, changes in TG, SUA and GGT were significantly associated with changes in HOMA-IR. In addition to their direct associations, we observed a synergistic association between changes in TG and SUA and changes in HOMA-IR. Participants were divided into three groups (tertiles) according to changes in TG and SUA. The tertiles of changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Differences in uric acid levels were statistically significant in both groups, whereas changes in glucose levels were significant only in the combined exercise group. It has been shown that walking program which is 120 minutes per week for 12 weeks does not change uric acid level in elderly women (Kawamoto et al, 2016). In another study, moderate intensity exercises were performed for 8 weeks in subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in uric acid levels were statistically significant in both groups, whereas changes in glucose levels were significant only in the combined exercise group. It has been shown that walking program which is 120 minutes per week for 12 weeks does not change uric acid level in elderly women (Kawamoto et al, 2016). In another study, moderate intensity exercises were performed for 8 weeks in subjects with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in the obese participants may have been due to a higher absolute energy expenditure in obese females compared to the lean females during PA [34] despite lower daily steps count. Researchers found that, after 12 weeks of training, there was a decrease in the TG levels, together with a drop in the insulin resistance indicator [35]. Similarly, Hong et al indicated that exercise could positively enhance markers of insulin resistance with an increase in serum adiponectin levels in obese females [33].…”
Section: Discussionmentioning
confidence: 99%
“…Физическая активность Поддержание физической активности обладает рядом несомненных достоинств -улучшение общего самочувствия, профилактика хронических заболеваний, снижение смертности и контроль уровня стресса. Японские коллеги установили, что у 100 пациенток женского пола, находящихся в менопаузе, скандинавская ходьба позволила снизить не только уро-вень МК, но и уровень триглицеридов, а также инсулинорезистентность [48]. На о. Тайвань было проведено исследование, включавшее 467976 человек, 25% которых имели уровень МК выше 7,0 мг/дл (420 мкмоль/л).…”
Section: лечение бессимптомной гиперурикемии немедикаментозные методыunclassified